2019
DOI: 10.1016/j.jor.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Current literature on surgical checklists and handoff tools and application for orthopaedic surgery

Abstract: Despite the adaptation of checklists for specific surgeries being developed, there remains a lack of an available standard for an orthopaedic-specific checklist. Benefits of implementing checklists include cost-effectiveness as well as the ability to significantly reduce both mortality and complication rates in a variety of healthcare settings. The aim of this review is to analyze the evidence surrounding the effectiveness of checklists as well as recommend for the development of a standard checklist for speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Within orthopaedics, previous efforts to improve communication and patient care have centered around preoperative and postoperative checklists. 12,13 In contrast, Gagnier et al 14 developed a handoff tool for orthopaedic trauma residents and evaluated its effect on adverse events. After interdisciplinary design and pilot testing, the handoff tool was implemented and data were collected for 127 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Within orthopaedics, previous efforts to improve communication and patient care have centered around preoperative and postoperative checklists. 12,13 In contrast, Gagnier et al 14 developed a handoff tool for orthopaedic trauma residents and evaluated its effect on adverse events. After interdisciplinary design and pilot testing, the handoff tool was implemented and data were collected for 127 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prior efforts to improve patient handoffs in orthopaedics have described the development of handoff criteria de novo through surveys and focus groups. Sleiman et al 15 conducted a review of current literature on surgical checklists and handoff tools for orthopaedic surgery. They emphasized the potential for checklists to improve cost-effectiveness and reduce both mortality and complications, but they noted a lack of orthopaedic-specific tools.…”
Section: Discussionmentioning
confidence: 99%
“…Examples in medicine include the use of surgical safety checklists and standardized order sets. 26 , 27 The previous literature has shown that carefully developed and well-implemented checklists are effective in error prevention, standardization of management, and performance improvement in patient care. 23 – 25 Clinical guidelines and best practices in stroke have been established and published by several professional organizations worldwide.…”
Section: Special Projectsmentioning
confidence: 99%